B lymphocytes undergo TLR2-dependent apoptosis upon Shigella infection - Nothelfer, Katharina (The Rockefeller University Press, 2014)
Antibody-mediated immunity to Shigella, the causative agent of bacillary dysentery, requires several episodes of infection to get primed and is short-lasting, suggesting that the B cell response is functionally impaired. We show that upon ex vivo infection of human colonic tissue, invasive S. flexneri interacts with and occasionally invades B lymphocytes. The induction of a type three secretion apparatus (T3SA)–dependent B cell death is observed in the human CL-01 B cell line in vitro, as well as in mouse B lymphocytes in vivo. In addition to cell death occurring in Shigella-invaded CL-01 B lymphocytes, we provide evidence that the T3SA needle tip protein IpaD can induce cell death in noninvaded cells. IpaD binds to and induces B cell apoptosis via TLR2, a signaling receptor thus far considered to result in activation of B lymphocytes. The presence of bacterial co-signals is required to sensitize B cells to apoptosis and to up-regulate tlr2, thus enhancing IpaD binding. Apoptotic B lymphocytes in contact with Shigella-IpaD are detected in rectal biopsies of infected individuals. This study therefore adds direct B lymphocyte targeting to the diversity of mechanisms used by Shigella to dampen the host immune response.